V. S. Naipaul, Mimicry, and the Fictionalization of Caribbean Black Power in Guerrillas - Robert Kyriakos Smith (Literature, 2025)
V. S. Naipaul’s 1975 novel Guerrillas is the earliest example of Caribbean fiction that purports to provide a realistic depiction of Trinidad’s brief but historically significant Black Power movement. Naipaul was an Indo-Trinidadian expatriate who immigrated to the U.K. in 1950 and remained there until his death in 2018. He was famously Anglophilic; and given his notorious insistence that culturally the West Indies are derivative, not creative, it is unsurprising that Naipaul depicts Black Power as an empty form that Trinidad and Great Britain import to their detriment from the U.S. In its fictionalization of the story of a real-life figure on the periphery of Black Power, Guerrillas presents Black Power’s presence in Trinidad and the UK as a failure and a sham. My article traces Naipaul’s transformation of what was originally a journalistic account into his novel Guerrillas in order to highlight the tendentiousness of his representation of Trinidadian Black Power. The plot of the novel repurposes the crux of Naipaul’s essay “The Killings in Trinidad” in which he reports how a Trinidadian Black Power poseur known as “Michael X” conspired in the January 1972 murder of a white woman named Gale Ann Benson. Crucial to Naipaul’s dismissal of Black Power as a derivative fiction, this article argues, is the fraudulent Michael X, himself a mimic man par excellence in his embodiment of Black Power as an empty and parodic form devoid of original content. I demonstrate how Naipaul’s marginalization of Caribbean Black Power depends on formal mimicry and on his selection of this marginal player/mimic man as representative of the movement in Trinidad.